Current evidence for COPD management with dual long-acting muscarinic antagonist/long-acting β2-agonist bronchodilators. Issue 2 (17th February 2020) - Skolnik, Neil S.; Nguyen, Trang Susan; Shrestha, Aarisha; Ray, Riju; Corbridge, Thomas C.; Brunton, Stephen A.
ABSTRACT: Long-acting inhaled bronchodilator medications are recommended as initial maintenance therapy for many patients with COPD. These medications include long-acting muscarinic antagonists (LAMA) and long-acting β2 -agonists (LABA). Combinations of long-acting bronchodilator agents (LAMA/LABA) and inhaled corticosteroids combined with LABA (ICS/LABA) are also used as initial or follow-up therapy in patients with more severe symptoms or at risk of COPD exacerbations. This review summarizes the position of LAMA/LABA combinations in treatment recommendations, and the evidence supporting their placement relative to LAMA monotherapy and ICS/LABA combination therapy, as well as differences within the LAMA/LABA class. Most studies show that LAMA/LABA treatment leads to greater improvements in lung function and symptoms than LAMA monotherapy or ICS/LABA treatment. There are fewer studies comparing the impact of different medication classes on patients' risk of exacerbations; however, the available evidence suggests that LAMA/LABA treatment and LAMA monotherapy lead to a similar reduction in exacerbation risk, while the effect of LAMA/LABA compared with ICS/LABA remains unclear. The incidence of adverse events is similar with LAMA/LABA and LAMA alone. There is a lower risk of pneumonia with LAMA/LABA compared with ICS/LABA. This evidence supports the use of LAMA/LABA combinations as an initial maintenance therapy option for symptomatic patients with low exacerbation risk and severe breathlessness or patients with severe symptoms who are at risk of exacerbations, and as follow-up treatment in patients with uncontrolled symptoms or exacerbations on bronchodilator monotherapy.